PENURUNAN INTENSITAS NYERI PADA PASIEN FLEBITIS SETELAH PEMBERIAN KOMPRES HANGAT - chrisyen damanik (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Background: Intravenous therapy or IV therapy is one of the most used therapy method Thar caused phlebitis. It is an inflammation of the veins tunica intima with the characteristics of a reddish symptoms at insertion area or along the vein, pain and swelling. One of non pharmacological treatment for patient with phlebitis is by giving warm compress. So that, this research aimed to know the effects of warm compress treatment on decreasing pain intensity on patient with phlebitis. Research methods: This researh used quasi-experiments with One Group Pretest Posttest design by using 20 respondents. Each respondents, before and after intervention, are measured by using pain scale observation sheet. Then, the data were analyzed by Wilcoxon Signed Ranks Test with a significant p value ˂ α 0,05. Findings: This research reveals that warm compress treatment decreasing pain intensity on patient with phlebitis, before and after intervention, with p value 0,000 (p ˂ α 0,05), that average value of pain intensity before warm compress treatments intervention is 7,45 and average value of pain intensity after warm compress treatments intervention in 15 minutes is 2,70. Conclusions: There is a relationship between warm compress treatment with decreasing pain intensity in patients with phlebitis. Therefore, nurse, especially in inpatient unit, should give warm compress treatment as alternative method in decreasing pain intensity on patient with phlebitis.